Synergizing Information Technology and Business Management: Unlocking the Power of Integration - Winanto, Sujoko (International Journal of Education, Information Technology, and Others, 2024)
In today’s dynamic business landscape, the integration of information technology (IT) with effective management practices has emerged as a critical driver of organizational success and innovation. The primary objective of this study is to elucidate the significance of integrating IT solutions with managerial strategies to achieve organizational goals efficiently. Utilizing a library research methodology, this study draws upon a diverse range of literature, scholarly articles, case studies, and empirical research to analyze the integration of IT and business management comprehensively. Through a rigorous literature review and analysis, this research synthesizes various perspectives and theoretical frameworks to offer a holistic understanding of the subject matter. The findings underscore the transformative impact of integrating IT solutions with business management practices. By adopting innovative technologies such as data analytics, artificial intelligence, and cloud computing, organizations can gain actionable insights, automate routine tasks, and facilitate informed decision-making. Furthermore, the study highlights the challenges and opportunities associated with IT-business alignment, emphasizing the importance of strategic planning, organizational readiness, and continuous adaptation to technological advancements